Regression of bladder tumors in mice treated with interleukin 2 gene- modified tumor cells [published erratum appears in J Exp Med 1993 Jun 1;177(6):following 1831] (The Rockefeller University Press, 1993)
This study explored the use of interleukin 2 (IL-2) and interferon gamma (IFN-gamma) gene-modified tumor cells as cellular vaccines for the treatment of bladder cancer. The mouse MBT-2 tumor used is an excellent model for human bladder cancer. This carcinogen-induced tumor of bladder origin resembles human bladder cancer in its etiology and histology, and responds to treatment in a manner similar to its human counterpart. Using retroviral vectors, the human IL-2 and mouse IFN- gamma genes were introduced and expressed in MBT-2 cells. The tumor- forming capacity of the cytokine gene-modified MBT-2 cells was significantly impaired, since no tumors formed in mice injected intradermally with either IL-2- or IFN-gamma-secreting cells, using cell doses far exceeding the minimal tumorigenic dose of parental MBT-2 cells. Furthermore, mice that rejected the IL-2- or IFN-gamma-secreting tumor cells became highly resistant to a subsequent challenge with parental MBT-2 cells, but not to 38C13 cells, a B cell lymphoma of the same genetic background. To approximate the conditions as closely as possible to the conditions prevailing in the cancer patient, inactivated cytokine-secreting cells were used to treat animals bearing tumors established by orthotopic implantation of MBT-2 cells into the bladder wall of the animal. Treatment of mice carrying a significant tumor burden with IL-2-secreting MBT-2 cells had a significant inhibitory effect on tumor progression with extended survival. Moreover, in 60% of the mice the tumor regressed completely and the animals remained alive and free of detectable tumor for the duration of the observation period. Treatment of tumor-bearing animals with IL-2- secreting MBT-2 cells was superior to the use of cisplatin, a chemotherapeutic agent used in the treatment of bladder cancer. The therapeutic effect of IFN-gamma-secreting cells was minimal and treatment with unmodified MBT-2 cells had no effect on tumor growth or survival, showing that the parental MBT-2 cells were nonimmunogenic in this experimental setting. Most importantly, mice that exhibited complete tumor regression after treatment with IL-2-secreting MBT-2 cells became resistant to a subsequent challenge with a highly tumorigenic dose of parental MBT-2 cells, indicating that long-term immunological memory was established in the "cured" mice.